Analysis of Lexical Meaning in Absorption Words in the Book " Obat Dungu Resep Akal Sehat. Filsafat Untuk Republik Kuat" by Rocky Gerung - Sanjaya, Mia Tri; Muslim, Muslim (Global Education Journal, 2025)
This research was conducted because there has been no study on the analysis of lexical meaning and the process of foreign word absorption in the book "Obat Dungu Resep Akal Sehat: Filsafat untuk Republik Kuat" by Rocky Gerung. In addition, this study contributes to education by helping society understand the meaning of terms considered complex and assisting readers in comprehending the use of terms in their intended context. This research employs a qualitative method with data collection techniques including thoroughly reading the book, inventorying data, and classifying it according to the relevant theory. The analysis is carried out by categorizing loanwords into adoption, adaptation, translation, or creation, and explaining their lexical meanings. The findings indicate that there are three loanwords through adoption (forum, formal, gender), three words through adaptation (konsensus, konstituen, koheren), three terms through translation (Kampanye Hitam, Politik Relawan, Undang-Undang Khusus), and three terms created by Rocky Gerung (konstanta-konstanta sosio-kultural, post-praetorian, surplus arogansi). These findings highlight the combination of foreign language influence and creativity in enriching the Indonesian vocabulary.